2002
DOI: 10.1002/ajp.10033
|View full text |Cite
|
Sign up to set email alerts
|

Genetic assessment of a white‐collared×red‐fronted lemur hybrid zone at Andringitra, Madagascar

Abstract: We examined a purported lemur (Eulemur fulvus rufusxE. albocollaris) hybrid zone at Andringitra, Madagascar, using sequences from five genes (one mitochondrial gene (d-loop) and four nuclear introns (hemopexin, malic enzyme, ceruloplasmin, and microsatellite 26 flanking region)), from 60 individuals (E. albocollaris (n = 16), E.f. rufus (n = 14), E. collaris (n = 9), and purported hybrids from Andringitra (n = 21)). Diagnostic (d-loop and microsatellite 26) and private sites (all other genes) were found in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 29 publications
2
73
1
Order By: Relevance
“…Hybrids have been reported for Eulemur mongoz × Eulemur (f.) fulvus (Zaramody and Pastorini 2001), Eulemur (m.) macaco × E. (f.) fulvus at Manongarivo (Goodman and Schütz 2000), E. (m.) macaco × E. (m.) flavifrons Rabarivola et al 1991), and E. (f.) fulvus × E. (f.) rufus (Lehman and Wright 2000). Johnson and Wyner (2000), Johnson (2002), andWyner et al (2002) also reported a zone of hybridization between Eulemur (fulvus) albocollaris (now called E. cinereiceps) and E. (f.) rufus.…”
Section: Natural Hybridizationmentioning
confidence: 97%
See 2 more Smart Citations
“…Hybrids have been reported for Eulemur mongoz × Eulemur (f.) fulvus (Zaramody and Pastorini 2001), Eulemur (m.) macaco × E. (f.) fulvus at Manongarivo (Goodman and Schütz 2000), E. (m.) macaco × E. (m.) flavifrons Rabarivola et al 1991), and E. (f.) fulvus × E. (f.) rufus (Lehman and Wright 2000). Johnson and Wyner (2000), Johnson (2002), andWyner et al (2002) also reported a zone of hybridization between Eulemur (fulvus) albocollaris (now called E. cinereiceps) and E. (f.) rufus.…”
Section: Natural Hybridizationmentioning
confidence: 97%
“…There they occur as far north as the Mangoro River and the Onive River, as far to the southwest as Ivohibé at the southern end of the Andringitra Massif. Recent studies of Eulemur species by Sterling and Ramarason (1996), Johnson and Wyner (2000), and Wyner et al (2002) provide evidence of hybridization zones between E. rufus (here considered to be rufifrons), E. collaris and E. cinereiceps (then called albocollaris) in the region. Other reports of hybridization among Eulemur spp.…”
Section: Family Lemuridae Gray 1821mentioning
confidence: 97%
See 1 more Smart Citation
“…Hybridization among metazoans has traditionally been viewed as an unusual event, but a variety of genetic studies in the past few decades have shown that this phenomenon is rather common, especially between closely related taxa (Mallet 2005). Among primates, natural hybridization occurs in at least 26 of $233 Old World species (e.g., baboons, guenons, macaques, lemurs) in which hybridization occurs at intraspecific (Groves 1978;Lernould 1988), interspecific (Phillipsconroy and Jolly 1986;Samuels and Altmann 1986;Struhsaker et al 1988;Watanabe and Matsumura 1991;Bynum et al 1997;Evans et al 2001;Wyner et al 2002), and even intergeneric levels (Dunbar and Dunbar 1974;Jolly et al 1997). Among neotropical primates, only 8 of $132 New World species have been suggested to form hybrids in the wild (Coimbra-Filho et al 1993;Peres et al 1996;Mendes 1997) and these include only small-bodied and very recently separated taxa.…”
mentioning
confidence: 99%
“…Johnson (2004), Sterling and Ramaroson (1996), and Wyner et al (2002) have reported other Eulemur fulvus hybrid zones for white-collared brown lemurs (E. f. albocollaris) and collared brown lemurs (E. f. collaris) in SE Madagascar. Though Mittermeier et al (1994) suggested that hybrid forms of Eulemur fulvus fulvus may exist in eastern Madagascar, researchers have thought the Onive River separates the taxa from conspecifics.…”
Section: Discussionmentioning
confidence: 98%